Modelling shallow debris flows of the Coulomb-mixture type over temporally varying topography - Y. C. Tai; C. Y. Kuo (Natural Hazards and Earth System Sciences, 2012)
We propose a saturated binary mixture model for debris flows of the Coulomb-mixture type over temporally varying topography, where the effects of erosion and deposition are considered. Due to the deposition or erosion processes, the interface between the moving material and the stagnant base is a non-material singular surface. The motion of this singular surface is determined by the mass exchange between the flowing layer and the ground. The ratio of the relative velocity between the two constituents to the velocity of the solid phase is assumed to be small, so that the governing equations can be reduced to a system of the quasi-single-phase type. A shock-capturing numerical scheme is implemented to solve the derived equation system. The deposition shapes of a finite mass sliding down an inclined planary chute are investigated for a range of mixture ratios. The geometric evolution of the deposition is presented, which allows the possibility of mimicking the development of levee deposition.